2011
DOI: 10.1007/s10461-011-9927-9
|View full text |Cite
|
Sign up to set email alerts
|

Improving Clinic Attendance and Adherence to Antiretroviral Therapy Through a Treatment Supporter Intervention in Uganda: A Randomized Controlled Trial

Abstract: We assessed the effectiveness of the treatment supporter initiative as an intervention in improving clinic attendance for antiretroviral (ARV) drug refills and adherence to antiretroviral therapy (ART) in a cohort of HIV-infected adults. This two-arm randomized controlled trial was undertaken at an HIV clinic in a district hospital in Uganda. A total of 174 adult patients on ART were randomized 1:1 to a standard adherence intervention package plus a treatment supporter intervention (TS arm) or to a standard ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 32 publications
6
68
0
Order By: Relevance
“…Pt4 was an orphan who had lost his mother yet ART adherence problems among adolescents are aggravated by orphan-hood and lack of social support 15,19 . In Uganda, patient-selected treatment supporters improved ART treatment outcomes, especially at the start of ART [42][43] . Pt2 had no treatment supporter which hindered her ART adherence while the treatment supporter of Pt4 did not leave the ART medications to him or with another adult to supervise the intake.…”
Section: Discussionmentioning
confidence: 99%
“…Pt4 was an orphan who had lost his mother yet ART adherence problems among adolescents are aggravated by orphan-hood and lack of social support 15,19 . In Uganda, patient-selected treatment supporters improved ART treatment outcomes, especially at the start of ART [42][43] . Pt2 had no treatment supporter which hindered her ART adherence while the treatment supporter of Pt4 did not leave the ART medications to him or with another adult to supervise the intake.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of all the included HIV studies is reported in 74 Mozambique, 75 Switzerland, 76 Uganda, 77 South Africa, 78 and Nigeria. 79 The country in which the study was conducted was not reported in five studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…39,47,78,79,82 Interventions. Based on the factors responsible for poor adherence, the interventions were categorized as patient related (n = 31), 36 37,62,63,69,83 social and economic factors (n = 1), 77 and condition related (n = 1). 44 The interventions in thirty-nine of these studies targeted only the patient; …”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tangible/instrumental social support can range from making a meal for someone to driving that person to the doctor's office. In some situations, individuals need material goods or tangible actions to help them overcome challenging circumstances (Sherbourne & Stewart, 1991 (Kunutsor, 2011). Similarly, many studies have documented a direct relationship between tangible/instrumental social support and increased adherence to ART (Gonzalez et al, 2004, Ulett et al, 2009.…”
Section: Discussionmentioning
confidence: 99%